Pola Komunikasi Orang Tua dalam Membangun Kemandirian Anak Down Syndrome Studi Deskriptif Kualitatif Pola Komunikasi Orang Tua dalam Membangun Kemandirian Anak Down Syndrome di Kabupaten Bekasi - Dinda Salsabila (LITERATUS, 2023)
This study aims to find out, explore, and describe how and how big the role of parents is in building the process of independence in children with Down syndrome by using communication patterns, as well as providing learning to parents who have children with special needs with Down syndrome so that they are better at building independence in their children. This study uses a qualitative descriptive method within a constructivist paradigm. And in this study, the researchers used data collection techniques with interview techniques and direct observation of the field by seeing directly how the situation was in the field. The technique for determining informants in this study used purposive sampling by selecting six informants who were parents of children with special needs for Down syndrome and two informants who met the criteria specified in this study. The results of this study are to show that by using sign language and simple language, the message to be conveyed to children is easier to convey and will be easier for children with Down syndrome to understand. Parents who have children with special needs or Down syndrome teach independence to their children by using repeated explanation methods and by giving direct examples to the child so that children can easily imitate and understand what is being conveyed and what parents want.